Penerapan Model PBL Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Kelas IV Sekolah Dasar - Intan Kartikasari; Agung Nugroho; Aji Heru Muslim (Jurnal Gentala Pendidikan Dasar, 2021)
This research is purposed to improve critical thinking ability of students through Problem Based Learning (PBL) model application in Pengalusan 1 General Primary School. The media used to help this research is an audio visual media which is also a learning video. The type of this research is a class action research which includes 4 stages of activity in 1 cycle. The participants of this research are students of grade IV Pengalusan 1 General Primary School in 2nd semester of 2019/2020 school year, 28 students in total. The technic of data collection used consists of test and non test technic which involves observation and document. The result of this research shows that application of Problem Based Learning model is able to improve students’ critical thinking ability. The average of students’s ability in critical thinking is raised from 62.143 with percentage of completeness 50% becomes 71.4 with percentage of completeness 78.6%. The ability of critical thinking in students with problem based learning model can raise up through the syntax from problem based learning model which are in phase 1 student orientation of problem and phase 3 independent and club investigation. It is concluded that problem based learning model with the help of audio visual media can improve the ability of critical thinking in students of grade IV Pengalusan 1 General Primary School. Keywords: Critical thinking ability, Problem Based Learning